Studi Literatur: Identifikasi Jamur Dermatophyta Pada Pengrajin Batako - Anita, Anita; Junindar, Feby (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2022)
A brick maker is someone who works as a brick maker and has skills related to certain crafts. Workers who make bricks and do not pay attention to the use of personal protective equipment such as boots and gloves so that the range of workers is in direct contact with sand and water. Sand and water can increase the risk of fungal infections because sand and water are factors that trigger fungal growth, one of which is on nails. The fungi that often infect nails are dermatophytes. The purpose of this study was to determine the presence or absence of dermatophyte fungi present in the nail samples of brick makers. This research is a literature study that aims to utilize library sources to obtain data. The samples studied were journals, articles, and books related to the type of dermatophyte fungi with a total of 10 literatures. The method used in this study was a literature study. The results were obtained based on the results of a review of 10 literatures. From 142 samples, 75 samples were found that were positive for dermatophytes, with the types of fungi consisting of Trichophyton rubrum (20%), Trichophyton mentagtophytes (20%), and Epidermophyton floccosum (13%). So it can be concluded that from the average results, 53% of dermatophyte fungi were found in the nail samples of brick craftsmen.